Surface-enhanced Raman spectroscopy (SERS) study using oblique angle deposition of Ag using different substrates - Lee, Jaeyeong; Min, Kyungchan; Kim, Youngho; Yu, Hak Ki (Materials, 2019)
The oblique angle deposition of Agwith different deposition rates and substrates was studied for surface-enhanced Raman spectroscopy (SERS) efficiency. The deposition rate for the Ag substrate with maximum SERS efficiency was optimized to 2.4 Å/s. We also analyzed the morphology of Ag nanorods deposited at the same rate on various substrates and compared their SERS intensities. Ag deposited on SiO2, sapphire, and tungsten showed straight nanorods shape and showed relatively high SERS efficiency. However, Ag deposited on graphene or plasma-treated SiO2 substrate was slightly or more aggregated (due to high surface energy) and showed low SERS efficiency.
Keywords: Different substrates; High surface energy; Nano-gap; Oblique deposition; Oblique-angle deposition; SERS; Surface enhanced Raman spectroscopy; Various substrates; Ag nanogap; Oblique deposition; SERS